Reforming States, Agricultural Transformation, and Economic Development in Russia and Japan, 1853-1913 - Cohen, Mark (Conference Papers – American Sociological Association, 2015)
Capitalist economic development has occurred unevenly, as certain economies began sustained growth relatively early, opening up an increasingly large gap with lagging countries. This well-known fact has encouraged much research on the prospects for undeveloped economies to "catch up" to the earlier developers. Japan and Russia in the late nineteenth century were two of the first countries outside of western Europe to experience substantial catch-up growth. Beginning in the 1860s, political elites in both countries adopted wide-ranging reforms in pursuit of military modernization and its political and economic prerequisites. This paper analyzes the impact of the two states' reform programs on their countries' rural economies, which represented the vast majority of population and production. Adopting a Polanyian perspective on economic development, this paper finds that only in Japan were agrarian relations transformed so as to set off a process of capitalist economic development centered on rural areas. This divergence is explained by the different stances of the two reforming states towards landlords and peasant communities.
Sociology
Keywords: Japan; Russia; economic development; rural economies

Denaturalizing the Market: Primitive Accumulation, Class Reformation, and the Rise of Colombia's Anti-Neoliberal Countermovement - Hough, Phillip A. (Conference Papers – American Sociological Association, 2015)
This paper addresses what labor movement scholars are calling the "Polanyi-problem" - how societal movements can effectively re-embed neoliberal markets back into society - by drawing upon recent interpretations of Karl Marx writings on primitive accumulation and class formation. The author focuses on the case of Colombia's coffee farmers (cafeteros) - a class of producers whose historically-privileged modality of class reproduction was undermined by the liberalization of the coffee market in the 1990s and who have engaged in two major waves of protest aimed at re-embedding the coffee market back into society (1993-2001; 2013-2014). While similar in terms of movement targets, tactics, and general goals, a significant shift has occurred in the cafeteros' demands which is reflective of a fundamental transformation of their class identity away from one that 'naturalized' their dependence upon the coffee market to meet their subsistence needs and towards one that 'de-naturalizes' their dependence upon this market. This 'denaturalizatization of the market' undermined their ability to mobilize around a privileged form of class identity. Yet, it provided them with the ability to generalize their struggle beyond the confines of the coffee economy and therefore develop into a broad, national anti-neoliberal agrarian Polanyian counter-movement.
Sociology
Keywords: Colombia; Polanyi problem; countermovement; primitive accumulation; reembedding